Thermal Boundary Resistance in GaN Films Measured by Time Domain Thermoreflectance with Robust Monte Carlo Uncertainty Estimation. Issue 1 (2nd January 2016) - Bougher, Thomas L.; Yates, Luke; Lo, Chien-Fong; Johnson, Wayne; Graham, Samuel; Cola, Baratunde A.
ABSTRACT: In this work, we investigate the thermal boundary resistance and thermal conductivity of GaN layers grown on Si with 100 nm AlN transition layers using time domain thermoreflectance (TDTR). The GaN layers ranged from 0.31 to 1.27 μm. Due to the challenges in determining the thermal boundary resistance of the buried interfaces found in this architecture, a new data reduction scheme for TDTR that utilizes a Monte Carlo fitting method is introduced and found to dramatically reduce the uncertainty in certain model parameters. The results show that the GaN thermal conductivity does not change significantly with layer thickness, whereas the resistance of the AlN layer decreases slightly with GaN thickness.